Fibroblast Growth Factor 23 in Children with Chronic Kidney Disease - Muhammad Riza Kurniawan; Risky Vitria Prasetyo; Ninik Asmaningsih Soemyarso; Mohammad Sjaifullah Noer (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Decreased of glomerular filtration rate in chronic kidney disease (CKD) changes the calciumand phosphate balance. High phosphate levels in children with CKD stimulate secretion of FibroblastGrowth Factor 23 (FGF23). High FGF23 levels have harmful that potentially increase the morbidity andmortality of children with CKD.Objective: To analyze the level of FGF23 in children with CKD.Methods: A cross sectional study was performed in Pediatric Nephrology Ward and Outpatient Clinic ofDr. Soetomo General Hospital Surabaya, during December 2019-March 2020 for children with CKD stage1-5, aged 3 months to 18 years old. Children on phosphate-binder, vitamin D therapy, or severely ill wereexcluded. Blood level of FGF23 was measured using ELISA with statistic analysis with SPSS 20.Results: A total of 52 CKD stage 1-5 children were involved, mean age was 11.44 years old, and 50% wereboys. There were 51% children have FGF23 level more than 30 pg/ml. The lowest mean of FGF23 levelswas found in the CKD grade 1 (8.94 ± 8.77 pg/mL) and the highest mean at CKD grade 5 (113.30 ± 78.73pg/mL).Conclusion: The FGF23 level increasing accordance with increasing in the grade of CKD